Assessing the Co, Bi, and Mg Contents of Some Mineral Concrete Additives in terms of Environmental Effects - Ibrahi̇m Elajai̇l, Ibrahim Saleh; Şevi̇k, Hakan (Kastamonu University, 2022)
Concrete additives started to be used commonly in order to reduce the cost of concrete, which is widely used in construction industry, and to recycle some wastes that are harmful to the environment. However, these additives might include heavy metals that are very harmful to human and environmental health and the number of studies on this subject is very limited. Besides the health of individuals working in this industry, it also creates a lack of knowledge about the environmental effects of construction activities. In the present study, among the heavy metals that can be very harmful to human and environmental health, Co, Bi, and Mg concentrations in some concrete additives were examined. The results showed that heavy metal concentrations in various concrete additives including copper slag, vermiculite, brick dust, Cem III cement, and blast furnace slag were very high. It might pose a risk to the health of individuals working in this industry, as well as the environmental health.
Keywords: Engineering; Mühendislik; Concrete; Additive; Cobalt; Bismuth; Magnesium; 13. Climate action; 12. Responsible consumption